2013
DOI: 10.1021/am302989x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Plasma-Enhanced Chemical Vapor Deposition as a Method for Thin-Film Fabrication with Biological Applications

Abstract: Chemical vapor deposition (CVD) has been used historically for the fabrication of thin films composed of inorganic materials. But the advent of specialized techniques such as plasma-enhanced chemical vapor deposition (PECVD) has extended this deposition technique to various monomers. More specifically, the deposition of polymers of responsive materials, biocompatible polymers, and biomaterials has made PECVD attractive for the integration of biotic and abiotic systems. This review focuses on the mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 92 publications
0
80
0
Order By: Relevance
“…Deposition was carried out under low vacuum conditions, with low chamber pressure (0.03 Torr), low argon flow rate (99.99% purity, flow rate of 10 cm 3 /min), and low radio frequency power (30 W) . The RF power was pulsed with frequency ranging between 100 to 1000 Hz and duty cycles ranging from 25% to 100%, because previous studies have reported that using a low power pulsed plasma helps the activation as well as the retention of chemical activity of the deposited molecule . The morphology of the PECVD deposited di‐ d ‐phenylalanine nanotubes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition was carried out under low vacuum conditions, with low chamber pressure (0.03 Torr), low argon flow rate (99.99% purity, flow rate of 10 cm 3 /min), and low radio frequency power (30 W) . The RF power was pulsed with frequency ranging between 100 to 1000 Hz and duty cycles ranging from 25% to 100%, because previous studies have reported that using a low power pulsed plasma helps the activation as well as the retention of chemical activity of the deposited molecule . The morphology of the PECVD deposited di‐ d ‐phenylalanine nanotubes are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[3] The RF power was pulsed with frequency ranging between 100 to 1000 Hz and duty cycles ranging from 25% to 100%, because previous studies have reported that using a low power pulsed plasma helps the activation as well as the retention of chemical activity of the deposited molecule. [57,58] The morphology of the PECVD deposited di-D-phenylalanine nanotubes are shown in Fig. S1.…”
Section: Sample Preparationmentioning
confidence: 99%
“…[21,22] Plasma-enhanced chemical vapor deposition (PECVD) has been employed to synthesize PAMA. [23,24] The excessive energy from plasma, however, damaged allyl groups, resulting in a fully crosslinked polymer. [25] Compared with PECVD, initiated chemical vapor deposition (iCVD) is a much milder and more controllable method, thus more suitable for synthesizing functional thin films.…”
Section: Doi: 101002/macp201900299mentioning
confidence: 99%
“…Vapor‐based approaches could also compensate for the shortcomings caused by the use of organic solvents, such as insoluble reactants, residual contaminants from solvent, and damage to substrates . Plasma‐enhanced chemical vapor deposition (PECVD) has been employed to synthesize PAMA . The excessive energy from plasma, however, damaged allyl groups, resulting in a fully crosslinked polymer .…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances in the surface modification of materials have been made over the last decades and is increasingly becoming a common component in the design of biomaterials and medical devices. In early application, surface chemistry was modified in devices involved in blood‐contact applications (e.g., catheters, tubing, dialysis equipment) to prevent clot formation . Surface modification has also been used in multiple other applications to provide medical devices with enhanced wettability and antifouling properties as well as to enable grafting of bioactive agents for drug delivery applications .…”
Section: Introductionmentioning
confidence: 99%